Optimalisasi Chat GPT dan Canva AI sebagai Asisten Cerdas Guru Dalam Penyusunan Media Ajar - Muhamad Maksum Hidayat; Muhammad Syukron; Alvin Zuhair; Kukuh Trisna Pambudi; Antika Prasetyaningtyas; Muhammad Ichwandar Akrianto; Ahmad Nugroho (Comunitario: Jurnal Pengabdian Masyarakat, 2025)
In the digital era, teachers are required to produce creative and relevant teaching materials quickly. However, many teachers in rural areas, such as in Candimulyo District, still rely on manual methods that are time-consuming due to a lack of familiarity with modern technology. This community service aums to optimize the use of Artificial Intelligence (AI), specifically ChatGPT and Canva AI, as “smart assistans” to help teachers streamline their workload. The methods employed was a workshop with a hands-on training approach, guiding teachers to use AI for drafting lesson plans and designing visual media. The activity was attended by 30 teachers from LP Ma’arif. The evolution results showed a significant increase in competence. The average cognitive score rose from 83.33 (pre-test) to 100.00 (post-test) with an N-Gain of 0.48 (Medium Category). Furthermore, participants responded positively (score 4.19/5.00) regarding their ability to use these tools technically. It can be concluded that ChatGPT and Canva AI are effective in serving as smart assistants that increase teachers productivity and creativity in developing teaching materials.